2006
DOI: 10.1111/j.1365-2141.2006.06381.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organisation and regulation of murine alpha haemoglobin stabilising protein by erythroid Kruppel‐like factor

Abstract: SummaryAlpha haemoglobin stabilising protein (AHSP) binds free a-globin chains and plays an important role in the protection of red cells, particularly during b-thalassaemia. Murine ASHP was discovered as a GATA-1 target gene and human AHSP is directly regulated by GATA-1. More recently, AHSP was rediscovered as a highly erythroid Kruppel-like factor (EKLF) -dependent transcript. We have determined the organisation of the murine AHSP gene and compared it to orthologs. There are two CACC box elements in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
(79 reference statements)
2
22
0
1
Order By: Relevance
“…We expected KLF1 ChIP-seq peaks would be found at the proximal promoters of genes within the beta-globin gene cluster (e.g., Hbb-b1) (Im et al 2005;Keys et al 2007) and within the beta-globin LCR (Im et al 2005;Shyu et al 2006). Indeed, we observed KLF1 binding at the Hbb-b1 promoter and at HS1, HS2, HS4, and HS3 (weakly) of the beta-globin LCR (as defined in Hardison et al 1997) (Fig.…”
Section: Klf1 Occupies Cacc Motifs Located Proximally and Distally Tomentioning
confidence: 71%
See 3 more Smart Citations
“…We expected KLF1 ChIP-seq peaks would be found at the proximal promoters of genes within the beta-globin gene cluster (e.g., Hbb-b1) (Im et al 2005;Keys et al 2007) and within the beta-globin LCR (Im et al 2005;Shyu et al 2006). Indeed, we observed KLF1 binding at the Hbb-b1 promoter and at HS1, HS2, HS4, and HS3 (weakly) of the beta-globin LCR (as defined in Hardison et al 1997) (Fig.…”
Section: Klf1 Occupies Cacc Motifs Located Proximally and Distally Tomentioning
confidence: 71%
“…3A). Previous studies have also described KLF1 as a critical regulator of the gene encoding the alpha-globin chaperone protein Ahsp (Pilon et al 2006;Keys et al 2007). Unfortunately the Ahsp gene is missing from the mm8 and mm9 genome assemblies, preventing its inclusion in the comprehensive list of KLF1 ChIPseq target genes reported in this study.…”
Section: Klf1 Erythroid Regulatory Networkmentioning
confidence: 85%
See 2 more Smart Citations
“…Array data and direct analysis have shown that the AHSP promoter is another EKLF-dependent transcriptional target that is highly expressed in erythroid cells (22,37,52). However, its promoter contains neither an INI nor a DPE.…”
Section: Discussionmentioning
confidence: 99%